HELP THE ROHINGYA CHILDREN ON HUMANITARIAN GROUNDS - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 10 July 2015 – Development for the Rohingya children in the aspects as human resources and in their education would need to continue based on humanitarian grounds as well as a sign of solidarity and showing concern for their future.